Formulasi Sediaan Sabun Mandi Padat Dari Ekstrak Etanol Daun Kedondong (Spondias pinnata (L.f) Kurz) - Hasma Hasma; Erna Kadrianti (State University of Gorontalo, 2022)
Healthy skin is an element of female beauty. The thing that supports it is with cosmetics. The rise of the